2021
DOI: 10.1186/s13756-021-01037-z
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review on current duodenoscope reprocessing techniques and novel developments

Abstract: Duodenoscopy-associated infections occur worldwide despite strict adherence to reprocessing standards. The exact scope of the problem remains unknown because a standardized sampling protocol and uniform sampling techniques are lacking. The currently available multi-society protocol for microbial culturing by the Centers for Disease Control and Prevention, the United States Food and Drug Administration (FDA) and the American Society for Microbiology, published in 2018 is too laborious for broad clinical impleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 113 publications
0
11
0
Order By: Relevance
“…Taking into account all factors that may have an impact on the efficacy of an endoscope sampling method [6,15], it is highly probable that some studies may have underestimated the real contamination level of endoscopes and, therefore, they should be considered with caution in any comparison or attempt to define the threshold limit for endoscope contamination level. As stated by Heuvelmans et al [34] and Kenters et al [35], there is a real need to develop a standardized sampling protocol for endoscopes, including common interpretation criteria to allow any healthcare facility to evaluate the real risk associated with use of their endoscopes and facilitate evaluation of the impact of any new reprocessing method or process.…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account all factors that may have an impact on the efficacy of an endoscope sampling method [6,15], it is highly probable that some studies may have underestimated the real contamination level of endoscopes and, therefore, they should be considered with caution in any comparison or attempt to define the threshold limit for endoscope contamination level. As stated by Heuvelmans et al [34] and Kenters et al [35], there is a real need to develop a standardized sampling protocol for endoscopes, including common interpretation criteria to allow any healthcare facility to evaluate the real risk associated with use of their endoscopes and facilitate evaluation of the impact of any new reprocessing method or process.…”
Section: Discussionmentioning
confidence: 99%
“…Reusable devices can be prone to failure in sterilization or cleaning processes, posing a risk to subsequent patients. While enhanced surveillance and reprocessing methods were proposed, their superiority over standard HLD could not be consistently demonstrated 4,29,30 . Moreover, the adoption of enhanced surveillance and reprocessing methods raises the operational expenses with significant negative financial impact on the organizations 31 .…”
Section: Single‐use Duodenoscopes and Endoscopesmentioning
confidence: 99%
“…Some of the outbreaks were associated with deviation from standard disinfection protocols highlighting the importance of strict adherence to high‐level disinfection (HLD) protocols 2,3 . The fact that adequate reprocessing and adherence to protocols could not entirely eliminate bacterial contamination was explained by the complex design of the reusable duodenoscopes (especially the distal end) and endoscopic accessories 4 . As such, eliminating the reuse of the devices and accessories seemed to be the picture‐perfect remedy for cross‐infection associated with reusable devices.…”
Section: Introductionmentioning
confidence: 99%
“…The nosocomial infection incidence caused by multidrug-resistant organisms (MDROs) following endoscopic retrograde cholangiopancreatography (ERCP) investigations has been one of the most alarming developments in recent years . A cutting-edge medical procedure called ERCP, which was first used in 1968, is intended to make a noninvasive examination for diagnosis and treatment of pancreaticobiliary illnesses. , Duodenoscopes are difficult to properly be sterilized due to their complex structure. Duodenoscope contamination rates after reprocessing range from 0.4 to 35.8%. The most nosocomial infections are related to microbial adhesion to duodenoscopes. The most common pathogens known for their capacity to form an MDRO and attach to surfaces and areas that are challenging to access for reprocessing are Salmonella faecalis, Pseudomonas aeruginosa, Escherichia coli, and Klebsiella pneumoniae. Our previous research studies showed how sterilization cycles affected the duodenoscope, highlighting usage-related alterations to the coatings and working channel polymers and proving that the external coating is harmed gradually from the distal to the proximal part, ending with the elevator. , The stated rates of contamination on the duodenoscope show that the present reprocessing techniques are insufficient.…”
Section: Introductionmentioning
confidence: 99%